(3QSGdI aj GdRjGQIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPG cJGH cJHg GdTjN CHj SYjO Hf CHh GdNjQ bOS SQg Edi GdTjN GdQFjS GHf SjfG ai eYfi GdRjGQI hcjajI JCKjQgG jSe Gddg GdQMef GdQMje CeG HYO aCSCd ehdGi hcjajI GdRjGQI hMbjbJgeG hJCKjQgG s
(3BNQgG (B:s
(3dEfcTGa GdfYe GdeJUdI HGdfaS GdfGWbI agOGfG Gdgd hZjGc Edi JNdjU GdfaS ef ThGFH gPG GdeYQV JeJ hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs